Novel Caryophyllane-Related Sesquiterpenoids with Anti-Inflammatory Activity from Rumphella antipathes (Linnaeus, 1758) - Chang, Yu-Chia (Mar Drugs, 2020)
Two previously undescribed caryophyllane-related sesquiterpenoids, antipacids A (1) and B (2), with a novel bicyclo[5.2.0] core skeleton, and known compound clovane-2β,9α-diol (3), along with rumphellolide L (4), an esterified product of 1 and 3, were isolated from the organic extract of octocoral Rumphella antipathes. Their structures, including the absolute configurations were elucidated by spectroscopic and chemical experiments. In vivo anti-inflammatory activity analysis indicated that antipacid B (2) inhibited the generation of superoxide anions and the release of elastase by human neutrophils, with IC(50) values of 11.22 and 23.53 μM, respectively, while rumphellolide L (4) suppressed the release of elastase with an IC(50) value of 7.63 μM.